Imaging Early Steps of Sindbis Virus Infection by Total Internal Reflection Fluorescence Microscopy - Youling Gu; Yuanzheng Yang; Yuechueng Liu (Advances in Virology)
Sindbis virus (SINV) is an alphavirus that has a broad host range and has been widely used as a vector for recombinant gene transduction, DNA-based vaccine production, and oncolytic cancer therapy. The mechanism of SINV entry into host cells has yet to be fully understood. In this paper, we used single virus tracking under total internal reflection fluorescence microscopy (TIRFM) to investigate SINV attachment to cell surface. Biotinylated viral particles were labeled with quantum dots, which retained viral viability and infectivity. By time-lapse imaging, we showed that the SINV exhibited a heterogeneous dynamics on the surface of the host cells. Analysis of SINV motility demonstrated a two-step attachment reaction. Moreover, dual color TIRFM of GFP-Rab5 and SINV suggested that the virus was targeted to the early endosomes after endocytosis. These findings demonstrate the utility of quantum dot labeling in studying the early steps and behavior of SINV infection.